Biomass carbon catalyst as well as preparation method and application thereof

By preparing amorphous-transition-crystalline symbiotic biomass carbon catalysts, the existing catalyst preparation process is complicated, high cost and weak activity is solved, and efficient and stable H2O2 production is achieved, with the potential for large-scale application.

CN119843307APending Publication Date: 2025-04-18HENAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510048877.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing catalysts used for electrocatalytic redox production of H2O2 are complex in the preparation process, high cost and weak catalyst activity, which limit their large-scale application.

Method used

A biomass carbon catalyst is used to prepare a biomass carbon catalyst, by pre-carbonizing pine wood powder, soaking in acid, mixing with sodium carbonate and melamine, and then carbonizing treatment, forming a carbon structure with amorphous-transition-crystalline symbiotic symbiotic, thereby improving catalytic activity.

Benefits of technology

This biomass carbon catalyst has high catalytic activity, with a selectivity of 90% to H2O2, a Faraday efficiency of 95.02%, and maintains excellent stability in long-term continuous testing, with the potential for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843307A_ABST
    Figure CN119843307A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalysis, and discloses a biomass carbon catalyst as well as a preparation method and application thereof. The biomass carbon catalyst has a symbiotic structure of amorphous carbon, transition carbon and crystalline carbon. The preparation method comprises the following steps: by taking pine wood powder with large stock and low cost as a raw material, pre-carbonizing to obtain a precursor (BC), mixing the precursor (BC) with melamine and sodium carbonate, and carbonizing in a nitrogen atmosphere to obtain the biomass carbon catalyst. The catalyst has high H2O2 selectivity and activity, and can directly catalyze O2 to generate H2O2. The prepared material has good stability in the aspect of generating H2O2 through electro-catalysis of O2, and is a catalyst for generating H2O2 through electro-catalysis of O2, and the catalyst is low in cost, environmentally friendly and huge in application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a biomass carbon catalyst. Background Art

[0002] Hydrogen peroxide (H 2 O 2 ) is an important industrial chemical and a versatile benign oxidant, playing a vital role in a variety of applications ranging from chemical synthesis to potential energy carriers, from disinfection first aid kits to sewage treatment, from bleaching to aircraft propulsion. 2 O 2 It is industrially produced through a multi-step, energy-intensive anthraquinone process, which requires large infrastructure and produces a large amount of organic by-products, which has a negative impact on the environment and a heavy carbon footprint. 2 and O 2 Producing H on site 2 O 2 , but this process will bring safety issues (hydrogen and oxygen mixture is prone to explosion).

[0003] Electrocatalytic O 2 Reduction to produce H 2 O 2 It is considered to be a promising way to replace the current industrial anthraquinone oxidation / reduction process. The electrocatalytic process can be driven by clean energy such as solar energy and wind energy. It is green and environmentally friendly, has low production cost, mild reaction conditions, and low risk factor. It can effectively solve the high cost and environmental unfriendliness of anthraquinone process equipment and the direct mixing of H 2 and O 2 security issues.

[0004] Currently used for cathode oxygen reduction to produce H 2 O 2 The catalysts used in the production of catalytic converters mainly include noble metals and their alloys, transition metal-nitrogen-carbon complexes (MNCs), and carbon materials. Metal-based catalysts, such as noble metals Au, Pt, and Pd-Au, are synthesized from O 2 Electrosynthesis of H 2 O 2 Transition metal-nitrogen-carbon complex (MNC) catalysts have been shown to have high oxygen reduction catalytic activity, but most MNC catalysts follow the four-electron oxygen reduction (4e - ORR, electrocatalytic oxygen reduction to produce hydrogen peroxide follows 2e - ORR pathway) pathway, leading to the catalyst's 2 O 2 The selectivity is low.

[0005] Carbon materials have attracted people's attention due to their low price, abundant reserves and easy regulation. They are widely used in the field of electrocatalysis. Chinese patent application CN114014315A discloses a macroporous graphitized biomass carbon prepared by a molten salt chemical activation method, and tests its hydrogen evolution performance. The prepared biomass carbon has better stability and catalytic efficiency as a Pt / C catalyst carrier than commercial carbon black on the market. - There are also reports on the use of carbon materials as catalysts in the ORR field (LIM JS, KIM JH, WOO J Designing highly active nanoporous carbon H 2 O 2 production electrocatalysts through active site identification[J].Chem, 2021, 7(11):3114-3130.) By identifying the active oxygen functional groups and key structural factors and optimizing them, a high H 2 O 2 The most active catalyst O-GOMC-5.5 showed excellent stability for 168 h. 2 O 2 FE is as high as 99%, and a large amount of H 2 O 2 , indicating that carbon materials have great potential in electrocatalysis of 2e - ORR has great potential in synthesizing hydrogen peroxide, but its use of mesoporous silica-alumina template (Al-SBA-15) through the hard template method to synthesize the catalyst is relatively complicated. Prior art CN109941995A discloses a method for preparing a heteroatom-doped biomass carbon material, which is prepared by a three-step method of carbonization, activation and heteroatom doping. The preparation process of this method is relatively complex, and industrial production is energy-intensive and costly. It mainly achieves high electrocatalytic activity through a large number of heteroatom (B and N) doping, and the yield of undoped C is low, only about 50%. In contrast, a new and simple strategy to improve the activity of the catalyst is proposed, which will be conducive to the large-scale application of carbon materials in the field of electrocatalytic oxygen reduction to produce hydrogen peroxide. Summary of the invention

[0006] In view of the technical problems of complex preparation process, high cost and weak catalyst activity of catalyst for producing hydrogen peroxide by electrocatalytic oxygen reduction, the present invention proposes a biomass carbon catalyst and its preparation method and application.

[0007] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0008] A method for preparing a biomass carbon catalyst, the steps are as follows:

[0009] (1) sieving pine wood powder to remove impurities; pre-carbonizing the sieved pine wood powder in an atmosphere furnace; naturally cooling to room temperature after the carbonization, grinding the obtained powder, and passing it through an 80-100 mesh sieve to obtain a powder;

[0010] (2) The powder obtained in step (1) is soaked in acid, washed and dried to obtain biomass carbon, which is recorded as BC;

[0011] (3) The BC obtained in step (2) is mixed with sodium carbonate and melamine, and carbonized in an inert atmosphere, and then washed and dried to obtain a biomass carbon catalyst.

[0012] Thanks to the catalytic effect of sodium carbonate, the amorphous carbon in the material transforms into crystalline carbon. At the same time, melamine generates graphite phase carbon nitride when heated, which acts as a template, and finally forms a coexistence structure of amorphous carbon, transitional carbon from amorphous to crystalline, and crystalline carbon. In this special structure, the crystalline region exposes abundant edge sites. Unlike the carbon atoms in the crystalline core region that are difficult to participate in catalysis, these edge sites are the main catalytic reaction sites. In addition, in the transition region from amorphous to crystalline, there are many lattice defects, and obvious lattice distortion and dislocation can be observed. These defects have unique electronic structures that can regulate the adsorption energy of oxygen and reaction intermediates, which is beneficial to the reduction of oxygen to hydrogen peroxide. Due to the above reasons, the material as a whole has relatively abundant active sites and a large number of active sites, thus having higher catalytic activity.

[0013] In the above step (1), the pre-carbonization atmosphere is nitrogen, the gas flow rate is 1-5 mL / min, the temperature is increased to 300-400° C. at a heating rate of 5-10° C. / min, and the temperature is kept for 2-3 h.

[0014] In the above step (2), the acid is a 2-3 mol / L HCl solution.

[0015] In the above step (3), the mass ratio of BC, sodium carbonate and melamine is 1:2:(0.5-1).

[0016] Furthermore, the mixing in step (3) refers to grinding BC, sodium carbonate and melamine in an agate mortar for 10-20 minutes.

[0017] In the above step (3), the carbonization is carried out at a heating rate of 5-10°C / min, from room temperature to 1000-1100°C, and the reaction time is 2-3h.

[0018] Furthermore, in step (3), the inert atmosphere is nitrogen, and the nitrogen flow rate is 1-5 mL / min.

[0019] The above-mentioned washing refers to washing with ultrapure water and anhydrous ethanol in sequence.

[0020] The drying temperature is 100-120°C and the drying time is 18-30h.

[0021] The biomass carbon catalyst prepared by the above preparation method has a coexisting structure of amorphous carbon, transitional carbon from amorphous carbon to crystalline carbon, and crystalline carbon.

[0022] The above-mentioned amorphous-transition-crystalline co-growth biomass carbon catalyst is 2 Synthetic H 2 O 2 The specific steps are as follows: grind the dried catalyst, add appropriate amount of isopropanol, ultrapure water and Nafion membrane solution, and obtain a uniform slurry by ultrasound. The slurry is evenly applied on the current collector as the working electrode, and the electrocatalytic experiment is carried out to measure H 2 O 2 of production.

[0023] The beneficial effects produced by the present invention are:

[0024] (1) Compared with the existing noble metals and their alloys, transition metal-nitrogen-carbon complex (MNC) catalysts, the amorphous-transition-crystalline symbiotic biomass carbon catalyst provided by the present invention has many advantages such as low price, abundant reserves and simple preparation.

[0025] (2) The present invention benefits from the catalytic effect of sodium carbonate, which causes the amorphous carbon in the material to transform into crystalline carbon. At the same time, melamine generates graphite phase carbon nitride when heated, which acts as a template, and finally forms a coexistence structure of amorphous carbon, transitional carbon from amorphous to crystalline, and crystalline carbon. In this structure, the crystalline region exposes abundant edge sites, and there are many lattice defects in the transition region from amorphous to crystalline, which effectively promotes the reduction of oxygen to hydrogen peroxide. Specifically, the biomass carbon catalyst prepared by the present invention has a high affinity for H 2 O 2 The average selectivity of hydrogen peroxide is 90% in the range of 0.3-0.5V (relative to reversible hydrogen electrode). In addition, it has a higher electrocatalytic 2e - The ORR activity, the Faradaic efficiency is 95.02% under -300mA current conditions, and the hydrogen peroxide concentration can reach 3610.08ppm.

[0026] (3) The amorphous-transition-crystalline symbiotic biomass carbon catalyst provided by the present invention has excellent stability. Under the condition of -300mA current, it maintains excellent catalytic activity in more than 100 hours of continuous testing, and the cell pressure of the electrolytic cell does not increase significantly, which has the potential for long-term large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 The synthetic flow chart of the biomass carbon catalyst of the present invention is shown in FIG.

[0029] Figure 2 It is the X-ray diffraction pattern of the biomass carbon catalyst of the present invention.

[0030] Figure 3 This is the element mapping diagram of the biomass carbon catalyst of the present invention.

[0031] Figure 4 It is the X-ray photoelectron spectrum of the biomass carbon catalyst of the present invention.

[0032] Figure 5 The electron paramagnetic resonance spectrum of the biomass carbon catalyst of the present invention is shown in FIG.

[0033] Figure 6 This is a Raman spectrum of the biomass carbon catalyst of the present invention.

[0034] Figure 7 This is a transmission electron microscope photograph of the biomass carbon catalyst of the present invention.

[0035] Figure 8 The biomass carbon catalyst prepared in Example 1 is 2 O 2 selectivity.

[0036] Fig. 9 The biomass carbon catalyst prepared in Example 1 was electrocatalyzed at 2e - H produced under different currents during ORR 2 O 2 Concentration and Faradaic efficiency plot.

[0037] Fig.10 The biomass carbon catalyst prepared in Example 1 was electrocatalyzed at 2e - Stability diagram of the ORR process. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] The preparation method of the biomass carbon catalyst of this embodiment, the synthesis flow chart is as follows Figure 1 As shown, the specific steps are:

[0041] (1) Pre-carbonization of pine wood powder: sieve the pine wood powder to remove impurities; pre-carbonize the sieved pine wood powder in an atmosphere furnace, and use high-purity N before heating. 2 The air in the furnace was replaced, and then N 2 The temperature was raised from room temperature to 300°C at a rate of 5°C / min under an atmosphere and kept for 2 hours. After the temperature was reached, the mixture was naturally cooled to room temperature. The obtained powder was ground and passed through an 80-mesh sieve.

[0042] (2) Soak the powder after sieving in step (1) in a 3 mol / L HCl solution for 24 h to remove the influence of metal elements, wash it repeatedly with ultrapure water until it is neutral (by suction filtration until the filtrate is neutral), and wash it with anhydrous ethanol for 3 times. Place the washed powder in a forced air drying oven and dry it at 105° C. for 24 h to obtain biomass carbon, recorded as BC.

[0043] (3) The BC obtained in step (2) was mechanically mixed in a mass ratio of BC, sodium carbonate and melamine of 1:2:0.5 (1.0033 g BC, 2.0066 g sodium carbonate and 0.5016 g melamine), ground in an agate mortar for 10 min, placed in a crucible and transferred to an atmosphere furnace for carbonization. Before heating, high purity N 2 Replace the air in the furnace, in N 2 The temperature was raised from room temperature to 1050°C under protection at a rate of 5°C / min and a gas flow rate of 1 mL / min. The reaction was carried out at 1050°C for 2 h and then cooled to room temperature (under N 2 The temperature was rapidly reduced from 1050°C to 500°C under the action of N 2 The powder was cooled to room temperature under a vacuum atmosphere. The powder was washed repeatedly with ultrapure water until it was neutral (by suction filtration until the filtrate was neutral), and washed with anhydrous ethanol for 3 times. The washed powder was placed in a forced air drying oven and dried at 105°C for 24 hours. After drying, a biomass carbon catalyst was obtained, which was marked as M-BC.

[0044] Figure 2 The X-ray diffraction pattern of the biomass carbon catalyst prepared in Example 1 is as follows: Figure 2 The crystal phase analysis shows that the sample is carbon material and does not contain other impurities.

[0045] Figure 3 This is the element mapping diagram of the biomass carbon catalyst prepared in Example 1. As shown in the figure, the main elements in the sample are carbon (C) element and a small amount of oxygen (O) element, and it contains almost no N element, which can explain that there is no N doping in the catalyst.

[0046] Figure 4 This is the X-ray photoelectron spectrum of the biomass carbon catalyst prepared in Example 1. As shown in the figure, the main components of the sample are C and O, and the peak of N1s is very weak. The percentage of each atom in the biomass carbon catalyst is shown in Table 1.

[0047] Table 1. Atomic percentages in X-ray photoelectron spectroscopy

[0048]

[0049] As can be seen from Table 1, the atomic percentage of N is only 1.73%, which further illustrates that the N content in the catalyst is very low and it is believed that the N element is not the main source of activity.

[0050] Figure 5 The electron paramagnetic resonance spectrum of the biomass carbon catalyst prepared in Example 1, as shown in the figure, shows a single peak, and the corresponding g factor is 2.0085, which proves the existence of defects in the sample.

[0051] Figure 6 The Raman spectrum of the biomass carbon catalyst prepared in Example 1 is shown in the figure. As shown in the figure, the biomass carbon catalyst (M-BC) prepared in Example 1 has obvious D peak and G peak. The D peak indicates the existence of defects in its structure, and the G peak belongs to SP 2 Hybridized in-plane stretching vibration.

[0052] Figure 7 The transmission electron micrograph and simulation diagram of the biomass carbon catalyst prepared in Example 1 successfully capture the coexistence structure of amorphous carbon (II), the transition state of amorphous crystallization graphitization (transition state carbon of amorphous carbon to crystalline state) (III) and crystalline carbon (I).

[0053] Example 2

[0054] The preparation method of the biomass carbon catalyst of this embodiment, the synthesis flow chart is as follows Figure 1 As shown, the specific steps are:

[0055] (1) Pre-carbonization of pine wood powder: sieve the pine wood powder to remove impurities; pre-carbonize the sieved pine wood powder in an atmosphere furnace, and use high-purity N before heating. 2 The air in the furnace was replaced, and then the furnace was heated at 3 mL / min N 2 The temperature was raised from room temperature to 300°C at a rate of 5°C / min under an atmosphere and kept for 2 hours. After the temperature was reached, the mixture was naturally cooled to room temperature. The obtained powder was ground and passed through an 80-mesh sieve.

[0056] (2) The powder after sieving in step (1) was soaked in a 3 mol / L HCl solution for 24 h to remove the influence of metal elements, and was repeatedly washed with ultrapure water until neutral, and washed with anhydrous ethanol for 3 times. The washed powder was placed in a forced air drying oven and dried at 105° C. for 24 h to obtain biomass carbon, which was recorded as BC.

[0057] (3) The BC obtained in step (2) was mechanically mixed in a mass ratio of BC, sodium carbonate and melamine of 1:2:0.5 (1.0015 g BC, 2.0030 g sodium carbonate and 0.5007 g melamine), ground in an agate mortar for 10 min, placed in a crucible and transferred to an atmosphere furnace for carbonization. Before heating, high purity N 2 Replace the air in the furnace, in N 2 The temperature was raised from room temperature to 1050°C under protection at a rate of 5°C / min and a gas flow rate of 1 mL / min. The reaction was carried out at 1050°C for 2 h and then cooled to room temperature (under N 2 The temperature was rapidly reduced from 1050°C to 500°C under the action of N 2 The washed powder was placed in a blast drying oven and dried at 105°C for 24 hours. After drying, an amorphous-transition-crystalline symbiotic biomass carbon catalyst (denoted as M-BC) was obtained. The biomass carbon catalyst of this embodiment was subjected to electrocatalysis. 2 Synthetic H 2 O 2 Performance test: After testing under the two-electrode system-300mA constant current condition, the Faradaic efficiency of hydrogen peroxide is 95.989% and the hydrogen peroxide concentration is 3653.13ppm.

[0058] Example 3

[0059] The preparation method of the biomass carbon catalyst of this embodiment, the synthesis flow chart is as follows Figure 1 As shown, the specific steps are:

[0060] (1) Pre-carbonization of pine wood powder: sieve the pine wood powder to remove impurities; pre-carbonize the sieved pine wood powder in an atmosphere furnace, and use high-purity N before heating. 2The air in the furnace was replaced, and then the furnace was heated at 5 mL / min N 2 The temperature was raised from room temperature to 300°C at a rate of 5°C / min under an atmosphere and kept for 2 hours. After the temperature was reached, the mixture was naturally cooled to room temperature. The obtained powder was ground and passed through an 80-mesh sieve.

[0061] (2) The powder after sieving in step (1) was soaked in a 3 mol / L HCl solution for 24 h to remove the influence of metal elements, and was repeatedly washed with ultrapure water until neutral, and washed with anhydrous ethanol for 3 times. The washed powder was placed in a forced air drying oven and dried at 105° C. for 24 h to obtain biomass carbon, which was recorded as BC.

[0062] (3) The BC obtained in step (2) was mechanically mixed in a mass ratio of BC, sodium carbonate and melamine of 1:2:0.5 (1.0008 g BC, 2.0016 g sodium carbonate and 0.5004 g melamine), ground in an agate mortar for 10 min, placed in a crucible and transferred to an atmosphere furnace for carbonization. Before heating, high purity N 2 Replace the air in the furnace, in N 2 The temperature was raised from room temperature to 1050°C under protection at a rate of 5°C / min and a gas flow rate of 1 mL / min. The reaction was carried out at 1050°C for 2 h and then cooled to room temperature (under N 2 The temperature was rapidly reduced from 1050°C to 500°C under the action of N 2 The washed powder was placed in a blast drying oven and dried at 105°C for 24 hours. After drying, an amorphous-transition-crystalline symbiotic biomass carbon catalyst (denoted as M-BC) was obtained. The biomass carbon catalyst of this embodiment was subjected to electrocatalysis. 2 Synthetic H 2 O 2 Performance test: After testing in a two-electrode system at a constant current of 300 mA, the Faradaic efficiency of hydrogen peroxide was 94.06% and the concentration of hydrogen peroxide was 3567.03 ppm.

[0063] Example 4

[0064] The preparation method of the biomass carbon catalyst of this embodiment, the synthesis flow chart is as follows Figure 1 As shown, the specific steps are:

[0065] (1) Pre-carbonization of pine wood powder: sieve the pine wood powder to remove impurities; pre-carbonize the sieved pine wood powder in an atmosphere furnace, and use high-purity N before heating. 2 The air in the furnace was replaced, and then the furnace was heated at 5 mL / min N 2The temperature was raised from room temperature to 300°C at a rate of 10°C / min under an atmosphere and kept for 2h. After the temperature was reached, the mixture was naturally cooled to room temperature. The obtained powder was ground and passed through an 80-mesh sieve.

[0066] (2) The powder after sieving in step (1) was soaked in a 3 mol / L HCl solution for 24 h to remove the influence of metal elements, and was repeatedly washed with ultrapure water until neutral, and washed with anhydrous ethanol for 3 times. The washed powder was placed in a forced air drying oven and dried at 105° C. for 24 h to obtain biomass carbon, which was recorded as BC.

[0067] (3) The BC obtained in step (2) was mechanically mixed in a mass ratio of BC, sodium carbonate and melamine of 1:2:0.5 (2.0065 g BC, 4.0130 g sodium carbonate and 1.0032 g melamine), ground in an agate mortar for 10 min, placed in a crucible and transferred to an atmosphere furnace for carbonization. Before heating, high purity N 2 Replace the air in the furnace, in N 2 The temperature was raised from room temperature to 1050°C under protection at a rate of 5°C / min and a gas flow rate of 5 mL / min. The reaction was carried out at 1050°C for 2 h and then cooled to room temperature (under N 2 The temperature was rapidly reduced from 1050°C to 500°C under the action of N 2 The washed powder was placed in a blast drying oven and dried at 105°C for 24 hours. After drying, an amorphous-transition-crystalline symbiotic biomass carbon catalyst (denoted as M-BC) was obtained. The biomass carbon catalyst of this embodiment was subjected to electrocatalysis. 2 Synthetic H 2 O 2 Performance test: After testing in a two-electrode system at a constant current of 200 mA, the Faradaic efficiency of hydrogen peroxide was 94.1% and the concentration of hydrogen peroxide was 2385.5 ppm.

[0068] Example 5

[0069] The preparation method of the biomass carbon catalyst of this embodiment, the synthesis flow chart is as follows Figure 1 As shown, the specific steps are:

[0070] (1) Pre-carbonization of pine wood powder: sieve the pine wood powder to remove impurities; pre-carbonize the sieved pine wood powder in an atmosphere furnace, and use high-purity N before heating. 2 The air in the furnace was replaced, and then N 2 The temperature was raised from room temperature to 400°C at a rate of 7°C / min under an atmosphere and kept for 3 h. After the temperature was reached, the mixture was naturally cooled to room temperature. The obtained powder was ground and passed through a 100-mesh sieve.

[0071] (2) The powder after sieving in step (1) was soaked in a 2 mol / L HCl solution for 24 h to remove the influence of metal elements, and was repeatedly washed with ultrapure water until neutral (by suction filtration until the filtrate was neutral), and washed with anhydrous ethanol for 3 times. The washed powder was placed in a forced air drying oven and dried at 100° C. for 30 h to obtain biomass carbon, which was recorded as BC.

[0072] (3) The BC obtained in step (2) was mechanically mixed in a mass ratio of BC, sodium carbonate and melamine of 1:2:0.75 (1.0033 g BC, 2.0066 g sodium carbonate and 0.7524 g melamine), ground in an agate mortar for 15 min, placed in a crucible and transferred to an atmosphere furnace for carbonization. Before heating, high purity N 2 Replace the air in the furnace, in N 2 The temperature was raised from room temperature to 1100°C under protection at a rate of 7°C / min and a gas flow rate of 5 mL / min. The reaction was carried out at 1100°C for 2 h and then cooled to room temperature (under N 2 The temperature rapidly dropped from 1100℃ to 500℃ under the action of N 2 The washed powder was placed in a blast drying oven and dried at 100°C for 30 hours. After drying, an amorphous-transition-crystalline symbiotic biomass-carbon catalyst (denoted as M-BC) was obtained. The biomass-carbon catalyst of this embodiment was subjected to electrocatalysis. 2 Synthetic H 2 O 2 Performance test: After testing in a two-electrode system at 200mA constant current, the Faradaic efficiency of hydrogen peroxide was 91% and the concentration of hydrogen peroxide was 2306.9ppm.

[0073] Example 6

[0074] The preparation method of the biomass carbon catalyst of this embodiment, the synthesis flow chart is as follows Figure 1 As shown, the specific steps are:

[0075] (1) Pre-carbonization of pine wood powder: sieve the pine wood powder to remove impurities; pre-carbonize the sieved pine wood powder in an atmosphere furnace, and use high-purity N before heating. 2 The air in the furnace was replaced, and then N 2 The temperature was raised from room temperature to 350°C at a rate of 5°C / min under an atmosphere and kept for 2.5 hours. After the temperature was reached, the mixture was naturally cooled to room temperature. The obtained powder was ground and passed through a 90-mesh sieve.

[0076] (2) The powder after sieving in step (1) was soaked in a 2.5 mol / L HCl solution for 24 h to remove the influence of metal elements, and was repeatedly washed with ultrapure water until neutral (by suction filtration until the filtrate was neutral), and washed with anhydrous ethanol for 3 times. The washed powder was placed in a forced air drying oven and dried at 120° C. for 18 h to obtain biomass carbon, which was recorded as BC.

[0077] (3) The BC obtained in step (2) was mechanically mixed in a mass ratio of BC, sodium carbonate and melamine of 1:2:1 (1.0033 g BC, 2.0066 g sodium carbonate and 1.0033 g melamine), ground in an agate mortar for 20 min, placed in a crucible and transferred to an atmosphere furnace for carbonization. Before heating, high purity N 2 Replace the air in the furnace, in N 2 The temperature was raised from room temperature to 1000°C under protection, with a heating rate of 10°C / min and a gas flow rate of 3 mL / min. The reaction was carried out at 1000°C for 3 h, and then cooled to room temperature (under N 2 The temperature rapidly dropped from 1000℃ to 500℃ under the action of N 2 The washed powder was placed in a blast drying oven and dried at 120°C for 18 hours. After drying, an amorphous-transition-crystalline symbiotic biomass carbon catalyst was obtained. The biomass carbon catalyst of this embodiment was subjected to electrocatalysis. 2 Synthetic H 2 O 2 Performance test: After testing in a two-electrode system at a constant current of 200 mA, the Faradaic efficiency of hydrogen peroxide was 86% and the concentration of hydrogen peroxide was 2180.2 ppm.

[0078] Application Examples

[0079] The working electrode was prepared using the biomass carbon catalyst of Examples 1-3 for electrocatalytic testing. 1 mg of the biomass carbon catalyst of Example 1 was mixed with 180 μL of isopropanol, 60 μL of ultrapure water, and 30 μL of a 5 wt% Nafion membrane solution, and a mixed slurry was obtained by ultrasound. 5 μL of the slurry was dropped onto the glassy carbon electrode of the rotating ring disk electrode for testing the selectivity of hydrogen peroxide using the rotating disk electrode. The process for determining the selectivity of commercial graphite for hydrogen peroxide was the same as in Example 1 above. Figure 8 In order to utilize the biomass carbon catalyst of Example 1 to 2 O 2 As shown in the figure, the prepared biomass carbon catalyst has a high selectivity for H 2 O 2The average selectivity of hydrogen peroxide in the range of 0.3-0.5 V (vs. reversible hydrogen electrode) is 90%, which is much higher than the 75.45% of commercial graphite.

[0080] 5 mg of the biomass carbon catalyst prepared in Example 1 was mixed with 400 μL of isopropanol, 200 μL of ultrapure water and 60 μL of 5 wt% Nafion membrane solution, and a mixed slurry was obtained by ultrasound. The obtained slurry was evenly applied to the central 5 cm × 5 cm area of ​​a 6 cm × 6 cm current collector (carbon paper) as a working electrode, and an electrocatalytic oxygen reduction experiment was carried out under a two-electrode system to determine the hydrogen peroxide production. The electrode was subsequently used for long-term stability testing. Fig. 9 To utilize the biomass carbon catalyst of Example 1 under different current conditions in the electrocatalytic process, 2 O 2 Concentration and Faraday efficiency. Under the condition of -50mA current, the Faraday efficiency was 92.32% and the hydrogen peroxide concentration was 584.65ppm, under the condition of -100mA current, the Faraday efficiency was 94.13% and the hydrogen peroxide concentration was 1194.19ppm, under the condition of -200mA current, the Faraday efficiency was 93.78% and the hydrogen peroxide concentration was 2377.71ppm, under the condition of -300mA current, the Faraday efficiency was 95.02% and the hydrogen peroxide concentration was 3610.08ppm, and under the condition of -400mA current, the Faraday efficiency was 88.61% and the hydrogen peroxide concentration was 4494.79ppm. Fig.10 In order to utilize the stability of the biomass carbon catalyst in Example 1 during the electrocatalytic process, the test was carried out under a current condition of -300 mA. As shown in the figure, there was no obvious attenuation of performance during the continuous test for more than 100 hours, a relatively high Faraday efficiency was maintained, and there was no obvious change in the cell pressure of the electrolyzer, indicating that the catalyst has extremely excellent stability and has the potential for large-scale application.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A biomass carbon catalyst, characterized in that: The biomass carbon catalyst has a coexisting structure of amorphous carbon, transition carbon from amorphous carbon to crystalline carbon, and crystalline carbon.

2. The method for preparing the biomass carbon catalyst according to claim 1, characterized in that: Here are the steps: (1) Pine wood powder is obtained by pre-carbonizing, grinding and sieving; (2) The powder obtained in step (1) is soaked in acid, washed and dried to obtain BC; (3) The BC obtained in step (2) is mixed with sodium carbonate and melamine, and carbonized in an inert atmosphere, and then washed and dried to obtain a biomass carbon catalyst.

3. The method for preparing the biomass carbon catalyst according to claim 2, characterized in that: The pre-carbonization in step (1) refers to heating the temperature to 300-400°C at a heating rate of 5-10°C / min and keeping the temperature for 2-3 hours.

4. The method for preparing the biomass carbon catalyst according to claim 3, characterized in that: The pre-carbonization atmosphere in step (1) is nitrogen, and the gas flow rate is 1-5 mL / min.

5. The method for preparing the biomass carbon catalyst according to claim 4, characterized in that: The acid in step (2) is a 2-3 mol / L HCl solution.

6. The method for preparing the biomass carbon catalyst according to claim 5, characterized in that: In the step (3), the mass ratio of BC, sodium carbonate and melamine is 1:2:(0.5-1).

7. The method for preparing a biomass carbon catalyst according to claim 6, characterized in that: In step (3), the carbonization is carried out at a heating rate of 5-10°C / min, from room temperature to 1000-1100°C, and the reaction is carried out for 2-3 hours.

8. The method for preparing the biomass carbon catalyst according to claim 7, characterized in that: The washing refers to washing with ultrapure water and anhydrous ethanol in sequence.

9. The method for preparing a biomass carbon catalyst according to claim 8, characterized in that: The drying temperature is 100-120° C. and the drying time is 18-30 h.

10. Use of the biomass carbon catalyst according to claim 1 in electrocatalytic synthesis of H2O2 from O2.

Citation Information

Patent Citations

  • Preparation and application of heteroatom doped biomass carbon material for producing hydrogen peroxide through electro-catalysis

    CN109941995A

  • Molten salt chemical activation method for preparing macroporous graphitized biomass carbon

    CN114014315A